KOMPARASI DAYA ONE AXIS SOLAR TRACKER BERBASIS SUDUT MATAHARI DAN FIX SOLAR PANEL - Gabriella Yolanda Krisanti; Tri Nurwati; Erni Yudaningtyas (Jurnal Mahasiswa TEUB, 2023)
Indonesia is located on the equator so it has abundant sunlight all year. Solar energy is a potential energy source that can serve as an alternative energy to generate electricity. Utilization of solar energy to produce electricity using a semiconductor device, namely solar panels. Solar panels that are commonly used are solar panels that do not follow the movement of the sun (fixed solar panels). The absorption of solar energy in solar panels can be increased by making solar panels follow the direction of the sun's movement or commonly called solar trackers. One type of one-way solar tracker movement refers to the azimuth side movement. The angular movement of the sun with reference to the azimuth side can be predicted using calculations. Calculation of the angular movement of the sun depends on the time and location of data collection which includes latitude, longitude, and time zone. The data is then processed and produces the sun's azimuth angle which is the reference for the movement of the solar tracker. Increased absorption of solar energy can be shown through the greater power efficiency between the solar tracker and fixed solar panels. The efficiency results for increasing the power of the solar tracker averaged 21.228% from the tests on April 15, 16, 17 and 30, 2023. Keywords: Solar Panel, Solar Tracker, Calculation of the Angle Movement of the Sun, Power